Water quality and health risk assessment of trace elements contamination in Ghodaghodi Lake, Sudurpaschim Province, Nepal (Nepal Journal of Environmental Science, 2021)
The contamination of trace elements (TEs) in freshwater sources has become an alarming issue globally. This study evaluates the contamination level of TEs, their spatial distributions, and the health risks in the Ghodaghodi Lake complex, Nepal. Altogether, ten water samples were collected, and As, Ba, Cd, Co, Cr, Cs, Cu, Li, Mn, Ni, Pb, Rb, Sc, Sr, Ti, Tl, V, Y, and Zn were determined by inductively coupled plasma mass spectrometry. The results revealed that Sr, Zn, Cu, As, Sc, and Rb were dominated TEs, contributing to the contamination. The principal component analysis and correlation matrices demonstrated both the geogenic and anthropic origin of the TEs in the lake. The water quality index (WQI=10.08) and hazard indices